Potential Uses of Sewage Sludge in Agricultural Production - Gilsanz, Juan Carlos; Leoni, Carolina; Schelotto, Felipe; Acuña, Ana (Agrociencia Uruguay, 2013)
In agricultural systems, soil amendments with organic matter are advised in order to minimize soil degradation. The organic matter originated at the household wastewater treatment facilities (PTARD) called sewage sludge originated at household wastewater treatment facilities (PTARD), called urban sludge, is a potential source of organic matter for agricultural use. In this work we aimed to evaluate the agronomic potential of domestic sewage sludge to be used as soil organic amendment in crop production and to evaluate the risk of crop and soil contamination with human pathogens. Along six lettuce crop cycles we compared the productivity and leaf tissue nitrate content where fresh and composted sewage sludge, chicken bed and chemical fertilizers were applied, all with an equal supply of N. In only one cropping cycle lettuce yields were lower than with chemical fertilization, and leaf tissue nitrates were always within the maximum thresholds allowed. No contamination of soil and lettuce leaves with human pathogens was detected. Among the 13 sewage sludge samples analyzed, fecal coliforms levels were highly variable, bacteria belonging to Salmonella genus were detected in seven samples and helminthes eggs were found in only one sample. The results indicate the potential of composted urban sludge as organic amendment. Nevertheless, the safe use of sewage sludge in food production will also depend on its levels of human pathogens and on other factors not analyzed in the present work, like the level of heavy metals and the time interval between application and crop harvest.